Degradation of oxytetracycline under autotrophic nitrifying conditions in a membrane aerated biofilm reactor and community fingerprinting - Celik, Aytekin; Casey, Eoin; Hasar, Halil (Elsevier Science Bv, 2018)
Pharmaceuticals in waterbodies are a growing concern due to their extensive uses and adverse effects on aquatic life. Oxytetracycline (OTC) is one of tetracycline antibiotic group used for treatment of animals and humans. This study evaluates the simultaneous oxidation of OTC and ammonium under autotrophic nitrifying conditions by using a membrane aerated biofilm reactor (MABR) as it provides an appropriate environment for the antibiotic-degrading bacteria. The results showed that MABR achieved fluxes of 1.62 mg OTC/m(2).d and 1117 mg N/m(2).d while the fluxes of O-2(J(OTC-O2)) utilized for OTC and NH4-N(J(NH4)-N-(O2)) oxidation were calculated to be 2.94 and 5105 mg O-2/m(2).d, respectively. Three transformation products, 4-Epi-OTC, alpha-Apo-OTC and beta-Apo-OTC, were identified and measured at ppb levels. The biofilm community comprised of Bacteria environmental samples, b-proteobacteria, CFB group bacteria, g-proteobacteria, d-proteobacteria and a-proteobacteria.
Keywords: Membrane aerated biofilm reactor; OTC degradation; Transformation products; Molecular diversity